Peningkatan Kepuasan Nasabah melalui Penerapan Model SERVQUAL Studi pada Nasabah BPR X di Kabupaten Malang - Ayu Dyah Kusumaningrum; Noermijati - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Purpose of this research is to analyze the effect of service quality dimensions, which include physical evidence, reliability, responsiveness, assurance, and empathy, on customer satisfaction of BPR X customers, Malang District. The research method is using explanatory research which defines the casualistic relation between variables by hypothesis tests. Population in this research is 171 micro business owners who are the common credit/loan users of BPR X, Malang District. Using Slovin formula and probability simple random-sampling method, samples of 64 respondents are generated, data are collected using questionnaire, then processed using multiple linear regression analysis. Findings show that physical evidence, reliability, responsiveness, assurance, and empathy affect customer satisfaction simultaneously. Partially physical evidence, reliability, responsiveness and assurance affect the customer satisfaction, while empathy doesn’t affect the customer satisfaction. The dominant variable is assurance. These findings are hoped to be an input for BPR management in Malang District to increase the service quality dimension in order to increase customer satisfaction.Keywords: physical evidence, reliability, responsiveness, assurance, empathy, servqual, customer satisfaction